Operational oceanography for the Marine Strategy Framework Directive: the case of the mixing indicator. (12th February 2016) - Fratianni, C.; Pinardi, N.; Lalli, F.; Simoncelli, S.; Coppini, G.; Pesarino, V.; Bruschi, A.; Cassese, M.L.; Drudi, M.
ABSTRACT: In this paper we show that operational oceanography products can be used to develop indicators as required by the Marine Strategy Framework Directive (MSFD). We present a mixing indicator that is calculated using MyOcean Marine Service reanalysis products. Seasonal climatology data of the Brunt–Väisäla frequency (BVF) were computed for 2001–2010 and the vertical mixing coefficient was defined. A vertical mixing indicator was then computed in order to differentiate between different mixing conditions depending on the seasons and differentiating between the shelf and the open ocean in the central Mediterranean Sea.